Osteogenesis Imperfekta dengan Bronkopneumonia: Sebuah Laporan Kasus - Meidayanti, Devi; Apriyana, Ninike; Fadhila, Syifa Rahmi; Syafni, Alma Nazelia; Ivytha, Ivytha; Ismail, Ismi Citra (CV. Jasa Sukses Abadi, 2024)
Osteogenesis imperfecta (OI) or what is known as brittle bone disease (brittle bone disease) is a group of rare disorders that are hereditary. Prenatal diagnosis of pregnancies at risk for OI with fetal ultrasonography in the early 2nd trimester is feasible and allows treatment. The patient, a 2 month 23 day old baby, came to Abdoel Moeloek Hospital accompanied by his family with crooked legs since birth and shortness of breath since 1 day before entering the hospital. Other complaints experienced by patients include fever, weight loss since birth, broken bones. On physical examination, it was found that the general condition looked seriously ill, compos mentis consciousness, pulse 162x/minute, breathing 70x/minute, temperature 37.6˚C, SpO2 95% with Nasa cannula 1 lpm, the patient's nutritional status seemed poor, with body length 39 cm, upper body 26 cm, lower body 13 cm, and arm span 24 cm. According to the WHO growth chart, namely BB/U-2–0SD (normal); PB/U <-3 SD (severly stunted), the conjunctiva is not anemic, the blue sclera is positive, there is no visible breathing in the nostrils, the lips are not cyanotic, the thorax shows subcostal retraction, the breath sounds sound vesicular, there are fine wet crackles and there is no wheezing while heart within normal limits. A complete blood test showed that hemoglobin decreased by 8.8 g/dL, and hematocrit decreased by 28%, MCV 87fL, MCH 28 pg, MCHC 32 g/dL, suggesting normochromic normocytic anemia. Babygram showed the impression of osteogenesis imperfecta. The patient was diagnosed with osteogenesis imperfecta with bronchopneumonia and normochromic normocytic anemia.